2017
DOI: 10.1007/s40843-017-9111-1
|View full text |Cite
|
Sign up to set email alerts
|

Fully bio-based, highly toughened and heat-resistant poly(L-lactide) ternary blends via dynamic vulcanization with poly(D-lactide) and unsaturated bioelastomer

Abstract: Inherent brittleness and low heat resistance are the two major obstacles that hinder the wide applications of poly(L-lactide) (PLLA). In this study, we report a fully biobased, highly toughened and heat-resistant PLLA ternary blend, which was prepared by dynamic vulcanization of PLLA with poly(D-lactide) (PDLA) and an unsaturated bioelastomer (UBE). The results indicated that during dynamic vulcanization PDLA cocrystallized with PLLA to form stereocomplex (SC) crystallites, which not only enhanced the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The storage moduli of CIPUs are higher than that of COPU and increase with increasing HS content in the full temperature range, indicating reinforced mechanical performance due to the enhanced stiffness. The storage modulus at high temperature can be used to evaluate the heat resistance of a material, because higher storage modulus demonstrates better tolerance to external loading [5,27,28]. The storage modulus of COPU is only 1.59 MPa and the value increases to 2.69, 3.29, 3.54, 13.67, 21.29 and 94.8 MPa for C9I1PU, C8I2PU, C7I3PU, C6I4PU, C5I5PU and C4I6PU, respectively, indicating enhanced heat resistance by incorporation of IS moiety.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage moduli of CIPUs are higher than that of COPU and increase with increasing HS content in the full temperature range, indicating reinforced mechanical performance due to the enhanced stiffness. The storage modulus at high temperature can be used to evaluate the heat resistance of a material, because higher storage modulus demonstrates better tolerance to external loading [5,27,28]. The storage modulus of COPU is only 1.59 MPa and the value increases to 2.69, 3.29, 3.54, 13.67, 21.29 and 94.8 MPa for C9I1PU, C8I2PU, C7I3PU, C6I4PU, C5I5PU and C4I6PU, respectively, indicating enhanced heat resistance by incorporation of IS moiety.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Exploitation of sustainable polymers from renewable feedstocks has attracted increasing attention, due to the continuously increased environmental concerns and resource crisis related to traditional fossil-based polymers [1][2][3][4][5][6]. Inexpensive vegetable oils, with various functional groups such as C=C double bond, ester, hydroxyl and epoxy groups depending on the origins, are thought as the ideal alternatives to fossil resources in production of novel sustainable polymers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the stereocomplexation of PLLA-PEG-PLLA/PDLA-PEG-PDLA blends improved the heat resistance of the blend films. The heat resistance of PLLA and scPLA has been widely investigated by DMA analysis from storage modulus as a function of temperature [37,38]. The storage modulus of lowcrystallinity PLLA dramatically dropped as the temperature passing the T g region before increasing again due to cold crystallization of PLLA during DMA heating scan.…”
Section: Resultsmentioning
confidence: 99%
“…The homo-and sc-crystallites of PLA had melting temperatures at lower and higher than 200 o C, respectively [20]. The scPLA showed better thermo-mechanical properties and heat resistance than PLLA due to faster crystallization of sccrystallites upon cooling [19,21,22]. However, scPLA with high PDLA contents or high content of sccrystallites have to be processed at high temperature (240 − 250 o C) which risks thermal decomposition [12, 23−25].…”
Section: Introductionmentioning
confidence: 99%